INFLUENCE OF THE BRONCHIAL ASTHMA, ALLERGIC RHINITIS AND ATOPIC DERMATITIS ON THE QUALITY OF THE CHILDREN'S LIFE - A.A. Dzhumagaziev; L.S. Namazova-Baranova; D.A. Bezrukova; O.A. Shelkova (Педиатрическая фармакология)
This article is devoted to the study of the life quality of the children, suffering from bronchial asthma, allergic rhinitis and atopic dermatitis. The authors identified that children with atopic dermatitis have the lowest level of the life quality, while children, suffering from allergic rhinitis, have the highest values of the given property. It is typical that children and their parents evaluate the life at school extremely low against rather high figures of the physical and emotional functioning.Key words: bronchial asthma, allergic rhinitis, atopic dermatitis, children, life quality.